HUBUNGAN ANTARA GANGGUAN POLA TIDUR DENGAN FLOUR ALBUS (KEPUTIHAN) PADA REMAJA - Aries Abiyoga; Gathut Pringgotomo; Nurul Azizah (ITKES Wiyata Husada Samarinda, 2018)
The Flour Albus is abnormal vaginal secretions in women. The Flour Albus caused by infection usually accompanied by itching in the vagina and around the outer lip of the vagina, often accompanied by a bad smell and cause pain during urination or intercourse. Impact of Flour Albus which is not handled and persistently disrupts the function of the woman reproductive organs with the occurrencesexually transmitted disease(STD) in young women.Factors that affect the occurrence Flour Albus is many kinds, one of which is the lack of sleep that makes hormones in the body is not balanced. The aim of this study is to determine the correlation between sleep pattern disturbance with the flour albus in young women. The study design was cross sectional approach. The sampels of this study are 60respondents with a simple random sampling technique.The study result was Kolmogorov-Smirnov test, there are 58respondents(96,7%)experience sleep pattern disturbance with frequent and occasionalcategories and42 respondents (70%) experience Flour Albus not normal. Indicated that the p value of 0,000 (<0,05).The conclusion of this study there was a correlation between sleep pattern disturbance with the flour albus. In suggesting to the respondents order to pay attention and raise awareness about good sleep patterns.